2017
DOI: 10.1016/j.jtho.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Completely Resected Node-Negative Lung Adenocarcinoma of 3 cm or Smaller

Abstract: The new adenocarcinoma classification has significant impact on recurrence in node-negative lung adenocarcinoma 3 cm or smaller. Patients with the micropapillary/solid predominant pattern have a significantly higher risk for recurrence. For tumors 2 cm or smaller, presence of the solid pattern was a prognostic factor for higher probability of recurrence. This information is useful for patient stratification for adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Their study showed that patients with the micropapillary and/or solid predominant patterns had signifi cantly higher risk for recurrence. This study also suggested that these patients could benefi t from adjuvant therapy [46]. In completely resected lung adenocarcinoma cases of less than 3 cm, micropapillary pattern was a signifi cant predictor of occult N2 lymph node metastasis in a study including 471 patients performed by Hung et al [47].…”
Section: Pro Gnostic Factors By Tumor Sizementioning
confidence: 59%
“…Their study showed that patients with the micropapillary and/or solid predominant patterns had signifi cantly higher risk for recurrence. This study also suggested that these patients could benefi t from adjuvant therapy [46]. In completely resected lung adenocarcinoma cases of less than 3 cm, micropapillary pattern was a signifi cant predictor of occult N2 lymph node metastasis in a study including 471 patients performed by Hung et al [47].…”
Section: Pro Gnostic Factors By Tumor Sizementioning
confidence: 59%
“…Previous studies on the postoperative prognosis of early stage lung adenocarcinoma mainly focused on stage I or IB. Hung et al [14] reported the prognosis predictive value of micropapillary/solid patterns in lung adenocarcinoma with tumor diameter ≤ 3 cm and lymph node negative. However, the study also included visceral pleural invasion, which is a known risk factor for poor prognosis in stage I lung adenocarcinoma [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Independent prognostic histopathologic factors have been published and include tumor size, 1 visceral pleural invasion, 2 lymphovascular invasion, 3 large cell neuroendocrine phenotype, 4 and micropapillary adenocarcinoma subtype. 5 Some investigators have moved to tumor molecular profiling and validated gene expression assays to risk stratify patients. 6 Others have assessed the predictive role of common driver mutations in resected early stage NSCLC.…”
Section: Michael Lanuti MDmentioning
confidence: 99%